Sistem Informasi Akademik Berbasis Web Pada Sekolah Menengah Kejuruan Negeri 2 Kota Bengkulu - Sihombing, Donny Moses; Aspriyono, Hari; Suryana, Eko (MEANS (Media Informasi Analisa dan Sistem), 2022)
The development of technology is currently very influential in the world of education. Inthis era of ever-increasing technology, it is required to work quickly and precisely. Likewise in the world of education, especially in vocational high schools, it is very necessary to have technology that is able to work in the field of school operations and for the smooth activities of students and teachers. Academic information system is a system built to assist educational institutions in managing student academic data, such as teacher data, student data, grade data, and other academic data. This system is used to make it easier to manage and display information related to academics. State Vocational High School 2 Bengkulu City is an institution engaged in the field of education that has utilized technology such as computers. However, at SMK Negeri 2 Bengkulu City, there is still no web-based academic information system. This study aims to create an Academic Information System at SMK Negeri 2 Bengkulu City. The research method used is the method of system design and development, such as the design of Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), Flowcharts, Databases (Files), Menus, Interfaces (Input/Output). Academic information system is made using CodeIgniter Framework, Hypertext Preprocessor (PHP) and MySQL database. The result of the research is that the academic information system created can assist in simplifying the data collection process for teachers, students, classes, making lesson schedules and assessments using a website-based academic information system.